Does transcription factor, induced by daptomycin and vancomycin, affect HIF-1α, Chondroadherin, and COL2A1? (Annals of Medical Research, 2021)
None
Keywords: CHAD; Chondrocytes; COL2A1; Daptomycin; HIF-1α; Vancomycin.